System identification of a prototype small scale ROV for depth control - Mohd Shahrieel, Mohd Aras; Shahrum Shah, Abdullah; Fadilah, Abdul Azis; Lim, Wee Teck; Ahmad Fadzli Nizam, Abdul Rahman (2015)
This paper present the design and development of a small scale underwater Remotely Operated Vehicle (ROV) and modelling the depth response of this ROV using System Identification Toolbox. The design of a small scale ROV has been done to minimize the hydrodynamic force and increase energy efficiency compared to the previous model that was developed by Underwater Technology Research Group (UTeRG). The performance of the designed ROV will be tested in UTeRG laboratory (lab tank test). The output signal from the pressure sensor (MPX4250GP) and the Inertial Measurement Unit (IMU) sensor are interpreted via an NI-card which was used for the data transfer. The prototype ROV was compared with the previous version in terms of depth control performance. System identification toolbox in MATLAB was used to infer a model from open-loop experiments. Then the obtained model was used to design a controller for the ROV. The focus of the controller design will be to ensure that the ROV is stable and can maintain position at a certain depth in a real underwater environment. After all the experiment has been conducted, the ROV managed to operate in a certain depth underwater using the controller designed successfully.